Identification of Health Status in Islamic Boarding School Students - Rejeki, Herni; Fijianto, Dwi; Rofiqoh, Siti; Widyastuti, Whinda (Konsorsium Lembaga Penelitian dan Pengabdian kepada Masyarakat Perguruan Tinggi Muhammadiyah 'Aisyiyah (PTMA) Koordinator Wilayah Jawa Tengah - DIY, 2022)
Health is a basic need for everyone. Health is often the impact of problems experienced by individuals as a result of unhealthy behavior. Medical examination should be carried out regularly by everyone to find out their health status. Identification to determine the health status at MBS Wonopringgo was done through physical examination, interviews and observations of students at MBS Wonopringgo. Physical examination included hair, eyes, teeth and mouth, neck, breasts, skin, genitalia, nails and feet. Interviews were conducted to obtain data on complaints felt in the last 6 months. The purpose of this community service was to obtain data on the health status of students at MBS Wonopringgo. The method used physical examination, observation and interviews. The results of this community service was identified the health status of students at MBS Wonopringgo. This data used as initial data in carrying out further community service research.